THE MYTH (& SOME MYTHS) OF TEACHING AMERICAN CULTURE - Patricia Dunkel (Indonesian JELT, 2013)
In this paper, the author opens by noting how culture influences outattitudes, emotions, beliefs, and values in pervasive ways. She thenasks how and why myths and generalizations emerge about theculture of various nation-states, regions, or even specific cocultureswithin these nations and regions. The simple answer is weform generalizations and develop myths to create comprehensibleframeworks of comparison regarding the systems of values andbeliefs held, and the codes of conduct followed by the majority ofthe people whose language we teach or study. We seek to createthese frameworks to interconnect the teaching of culture andlanguage, for usually language is taught as a system in (and of)itself, with its rules, exceptions, right answers and wrong answers.If culture is taught, it is usually infused into the language class inone of four common approaches. The author cites these fourcommon approaches to teaching culture: (1) the FrankensteinApproach, (2) the 4-F Approach, (3) the Tour-Guide Approach,and (4) the “By-The-Way” Approach); she warns of the inherentrisk involved in adopting any or all of these facile approaches, thatrisk being the creation and promulgation of cultural generalizations(even “myths”) that need tempering, and eventually revising.Referencing myths can make the teaching of culture easier, but itcan create problems when reality enters the scene. As an example,the author delves into a number of myths promulgated aboutAmericans university culture; these myths constitute sweepinggeneralizations that demand more greater and greater refinementand “reality checks.” The author ends with noting that “Americanculture” is a moving target that needs to be viewed as an evolvingentity that will continue to evolve and change as geopolitical,national, and regional events surface and cause continuous changein that moving target, American cultures.Keywords: myths, approaches to teaching culture;American cultures.